The compatibility of Islam with modernity : a brief discourse on Muslim reformists’ response - Owayemi, Musa Yusof; Mumtaz Ali, Mohammad (International Islamic University Malaysia, 2011)

(untitled)
Although the modern Western scholars have started discussing post-modernity, there is still an on-going debate on the issue of Islam and modernity in most Muslim nations and among Muslim scholars. The problem centres on what to do with modernity and what relationship could possibly be there between modernity and Islam. It seems that the views of the Muslim Reformists on the issue are radically different from those of the Muslim Revivalists. This article seeks to analyze the views of the Muslim Reformists on the issue of Islam and its compatibility with modernity.